2018
DOI: 10.1177/1367006918762158
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards Cypriot Greek and Standard Modern Greek in London’s Greek Cypriot community

Abstract: AimTo investigate whether the positive attitudes towards Standard Modern Greek and the mixture of positive and negative attitudes towards Cypriot Greek that have been documented in Cyprus are also present in London's Greek Cypriot community. ApproachUnlike previous quantitative works, the study reported in this article was qualitative and aimed at capturing the ways in which attitudes and attitude-driven practices are experienced by members of London's diasporic community. Data and AnalysisData were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 29 publications
2
8
1
Order By: Relevance
“…Further findings point to positive parental attitudes being directly associated with more successful maintenance (Hashimoto & Lee, 2011). Our results also agree with Polinsky (2011) and Karatsareas (2018) who report a similar positive stance among their participants towards their HL. Carreira and Kagan (2011: 48) found that most of their students had "largely positive feelings and experiences" with their HL.…”
Section: Profiles Identifies and Needs Of Greek Heritage Speakerssupporting
confidence: 91%
See 2 more Smart Citations
“…Further findings point to positive parental attitudes being directly associated with more successful maintenance (Hashimoto & Lee, 2011). Our results also agree with Polinsky (2011) and Karatsareas (2018) who report a similar positive stance among their participants towards their HL. Carreira and Kagan (2011: 48) found that most of their students had "largely positive feelings and experiences" with their HL.…”
Section: Profiles Identifies and Needs Of Greek Heritage Speakerssupporting
confidence: 91%
“…Carreira and Kagan (2011: 48) investigated HL learners' attitudes towards their HL and found that most of the students had "largely positive feelings and experiences" with their HL. Similar results were reported by Polinsky (2011), but also by Karatsareas (2018) who found a positive attitude among the members of the Greek-Cypriot Community in London towards their HL.…”
Section: Attitudes Towards the Hlsupporting
confidence: 89%
See 1 more Smart Citation
“…Widely accepted in Ukraine as a communicative tool, Russian is viewed very negatively by some older migrants and their descendants in the UK, even though all groups share the attachment to Ukrainian as a marker of their Ukrainian identity. Similar tensions are identified by Karatsareas (2018) in the Greek-speaking community of London, where Cypriot Greek is perceived by some as 'villagey' (Karatsareas 2018, 13), and in which Standard Modern Greek is the only variety taught in complementary schools where children are taught their community language. Teachers may correct heritage speakers when they use Cypriot Greek features; the use of Cypriot Greek features is also discouraged in informal settings, including the home.…”
Section: Introductionmentioning
confidence: 63%
“…Research on language attitudes has primarily focused on the attitudes towards standard and nonstandard language varieties (Dragojevic 2017). Karatsareas' (2018) The vitality of a language is reflected by the forces that lead to a shift in language use and in its symbolic value (Ryan, Giles & Sebastian 1982). Thus, the more a language is used as a means of communication in various social circles (inside and outside of the home) the higher its vitality.…”
Section: Linguistic History Of the Three Armenian Republics (1918-)mentioning
confidence: 99%